2017
DOI: 10.1155/2017/8257862
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-200c and miR-371-5p as the Useful Diagnostic Biomarkers and Therapeutic Targets in Kawasaki Disease

Abstract: Kawasaki disease (KD) has complexly clinical features and laboratory parameters and there is no definitive biomarker for this disease and the therapy of KD also is complex and uncertain. In this study, 102 KD patients and 80 healthy controls were enrolled in this study and the serum microRNAs were detected by qRT-PCR. The results showed that, compared with KD patients with a good response to high-dose intravenous immunoglobulin (IVIG) therapy, serum miR-200c and miR-371-5p were significantly higher in KD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In the included studies, the sample types of 3 studies were plasma, [ 25 – 27 ] and the remaining 3 studies were serum. [ 28 30 ] Besides, 3 studies defined healthy children as healthy controls (HCs), [ 26 , 27 , 29 ] 1 study defined juvenile systemic lupus erythematosus as the control, [ 25 ] 2 studies used both healthy and febrile children as controls. [ 28 , 30 ] Meanwhile, there were 2 types of reference miRNA, cel-miR-39, [ 25 , 27 , 28 , 30 ] and U6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the included studies, the sample types of 3 studies were plasma, [ 25 – 27 ] and the remaining 3 studies were serum. [ 28 30 ] Besides, 3 studies defined healthy children as healthy controls (HCs), [ 26 , 27 , 29 ] 1 study defined juvenile systemic lupus erythematosus as the control, [ 25 ] 2 studies used both healthy and febrile children as controls. [ 28 , 30 ] Meanwhile, there were 2 types of reference miRNA, cel-miR-39, [ 25 , 27 , 28 , 30 ] and U6.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 , 30 ] Meanwhile, there were 2 types of reference miRNA, cel-miR-39, [ 25 , 27 , 28 , 30 ] and U6. [ 26 , 29 ] The basic characteristics of the included studies were shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Rong et al [ 36 ] demonstrated that the serum miR-92a-3p levels were significantly higher in children with KD compared with non-Kawasaki disease subjects, and the miR-92a-3p level had a diagnostic sensitivity of 81.8% for KD. Zhang et al [ 37 ] enrolled 102 patients with KD and 80 healthy controls in a study and found that the serum miR-200c and miR-371-5p levels were significantly higher in the KD patients compared with the controls. These two miRNAs were significantly higher in KD patients who were resistant to IVIG compared with those for whom IVIG was effective; thus, these two miRNAs may serve as diagnostic biomarkers and therapeutic targets in KD.…”
Section: Discussionmentioning
confidence: 99%
“…miR-200c promotes endothelial cell apoptosis, inducing vascular smooth muscle cell inflammatory response and modulating TLR4 response [52]. Both miR-200c and -371-5p were shown to effectively distinguish between KD and healthy controls as well as IVIG-responsive and nonresponsive patients [53]. More recent research has identified new miRNAs with disease activity that potentially target vessel endothelial cell functions in KD patients [5458].…”
Section: Kawasaki Diseasementioning
confidence: 99%